Differentiation of epithelial cells in the urinary tract - Romih, R.; Korosec, P.; de Mello, W.; Jezernik, K. (Springer, 2005)
Uroplakins, cytokeratins and the apical plasma membrane were studied in the epithelia of mouse urinary tract. In the simple epithelium covering the inner medulla of the renal pelvis, no uroplakins or cytokeratin 20 were detected and cells had microvilli on their apical surface. The epithelium covering the inner band of the outer medulla became pseudostratified, with the upper layer consisting of large cells with stalks connecting them to the basal lamina. Uroplakins and cytokeratin 20 were not expressed in these cells. However, some superficial cells appeared without connections to the basal lamina; these cells expressed uroplakins Ia, Ib, II and III and cytokeratin 20, they contained sparse small uroplakin-positive cytoplasmic vesicles and their apical surface showed both microvilli and ridges. Cytokeratin 20 was seen as dots in the cytoplasm. This epithelium therefore showed partial urothelial differentiation. The epithelium covering the outer band of the outer medulla gradually changed from a two-layered to a three-layered urothelium with typical umbrella cells that contained all four uroplakins. Cytokeratin 20 was organized into a complex network. The epithelium possessed an asymmetric unit membrane at the apical cell surface and fusiform vesicles. Umbrella cells were also observed in the ureter and urinary bladder. In males and females, the urothelium ended in the bladder neck and was continued by a non-keratinized stratified epithelium in the urethra in which no urothelial cell differentiation markers were detected. We thus show here the expression, distribution and organization of specific proteins associated with the various cell types in the urinary tract epithelium.
Keywords: differentiation; urinary tract; urothelium; uroplakins; cytokeratins; mouse (Albany strain)